Poppaea Venus and the Ptolemaic Queens: An Alternative Biography - Gillespie, Caitlin (Histos, 2014)
This article examines the presentation of Nero’s wife Poppaea in the Oxyrhynchus papyrus fragment recounting her apotheosis (P.Oxy. LXXVII 5105). The poem arguably connects Poppaea to several Ptolemaic queens through characterizing Poppaea as a devoted wife, aligned with Aphrodite. The image of Poppaea as representative of a marriage ideal is largely absent from more familiar literary accounts. Through reconfiguring Poppaea as the Egyptianised wife of a godlike Nero, the poem increases the relevance of several aspects of Poppaea’s biography, including her devotion to Aphrodite during life, her embalmment after death, and her divinisation especially. This interpretation supports a probable first-century date of composition.